2012
DOI: 10.3144/expresspolymlett.2012.92
|View full text |Cite
|
Sign up to set email alerts
|

Effect of homopolymer poly(vinyl acetate) on compatibility and mechanical properties of poly(propylene carbonate)/poly(lactic acid) blends

Abstract: Abstract.A small amount of homopolymer poly(vinyl acetate) (PVAc) is used to compatibilize the biodegradable blends of poly(propylene carbonate) (PPC) and poly(lactic acid) (PLA). Scanning electron microscopy (SEM) and differential scanning calorimetry (DSC) results show that PVAc is selectively localized in the PLA phase and at the interface between PPC and PLA phases. As a result, these interface-localized PVAc layers act as not only a compatibilizer to improve the phase dispersion significantly but also a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 34 publications
4
39
0
Order By: Relevance
“…It show dark spherical particles (amorphous PPC) in the morphology of spherulites. Similar results are shown by POM [27] and SEM [8] . The size of this dark particles increased with the increasing PPC component in PLLA matrix.…”
Section: Differential Scanning Calorimeter (Dsc) Analysissupporting
confidence: 78%
See 2 more Smart Citations
“…It show dark spherical particles (amorphous PPC) in the morphology of spherulites. Similar results are shown by POM [27] and SEM [8] . The size of this dark particles increased with the increasing PPC component in PLLA matrix.…”
Section: Differential Scanning Calorimeter (Dsc) Analysissupporting
confidence: 78%
“…For example, the addition of a suitable amount of PVAc to both PMMA and PPC makes the blends fully miscible [20] . The addition of PVAc to the two immiscible polymers namely PLLA and PPC [7,9] served to improve the physical properties of the blend [8,21] . However, it has been demonstrated that increasing the PVAc in its blends with the PDLA [22] reduces the enzymatic degradation rate of PLLA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the two melting peaks of pure PHB shift to higher temperatures in all blends (from 131 to 138-156°C and from 147 to 154-167°C), this indicating better miscibility which can be favoured by the reduction in molecular mass of PHB during melting. The increase is less important in the blends containing 40 wt% or less PHB (EVA/PHB (70:30) is an exception); furthermore, the melting temperatures of the blends containing more than 50 wt% PHB are very similar ( [29] proposed the existence of physical crosslinking between PHB and different polymers (PLA, polypropylene carbonate -PPC -, polyvinyl acetate -PVAc), and the existence of interactions between the carbonyl (C=O) and methyl (CH 3 ) groups between PHB and PLA, and between PHB and PVAc in polymer blends have been supported in several studies [30][31][32][33][34][35][36]. The crystallinity of EVA, PHB and EVA/PHB blends was determined by X-ray diffraction.…”
Section: Results and Discussion 31 Characterization Of Eva+phb Blendsmentioning
confidence: 85%
“…The existence of physical interactions between EVA and PHB phases in EVA/PHB blends is evidenced by changes in compatibility, crystallinity and viscoelastic properties. The interactions between EVA or PVAc and PHB or PLA or PPC in polymer blends have been ascribed to the disruption of the interactions between the carbonyl (C=O) and methyl (CH 3 ) groups by weak physical interactions with C=O and CH 3 groups of PVAc [28][29][30][31][32][33][34][35][36]. Because of CH 3 and C=O groups also exists in the vinyl acetate domains in EVA, weak interfacial interactions between C=O and CH 3 groups of PHB and CH 3 and C=O groups of EVA can be produced.…”
Section: Proposed Mechanism Of the Interactionsmentioning
confidence: 99%